THE ALCAPA SYNDROME IN ADULTS - O. Ya. Vasiltseva; A. A. Boshchenko; A. A. Gorlova; N. N. Gladkikh; K. V. Zavadovsky; S. I. Vintizenko; B. N. Kozlov (Российский кардиологический журнал, 2018)
Syndrome of abnormal originating of the left coronary artery from pulmonary artery (ALCAPA), or Bland-White-Garland syndrome, is an inborn heart defect of atypical coronary arteries branching. In most cases this anomaly is revealed in infancy or adolescence. Opinions exist, that the anomaly is much more prevalent than it is diagnosed. Even more, it might be a cause of myocardial infarction and sudden death of 1st year newborns. In the article, a clinical case presented of first time revealed ALCAPA in 64 year old woman.